2011
DOI: 10.1007/s11695-011-0468-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Band Erosion in 63 Cases: Endoscopic Removal and Rebanding Evaluated

Abstract: Band erosion prevalence was 3.4%. Endoscopic removal of eroded gastric bands was proven safe and effective. Band erosion is now preferably managed endoscopically in our institution. Rebanding following erosion results in acceptable weight loss but an unacceptable reerosion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 16 publications
0
57
0
2
Order By: Relevance
“…Another study reported that endoscopic removal was attempted in 50 of 63 patients with band erosion, with a 92% success rate and a 10% complication rate. 29 A symptomatic pneumoperitoneum was the main complication reported in both studies. In our series, we removed the band endoscopically in 13 of 14 patients, with 3 patients requiring conversion to laparotomy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another study reported that endoscopic removal was attempted in 50 of 63 patients with band erosion, with a 92% success rate and a 10% complication rate. 29 A symptomatic pneumoperitoneum was the main complication reported in both studies. In our series, we removed the band endoscopically in 13 of 14 patients, with 3 patients requiring conversion to laparotomy.…”
Section: Discussionmentioning
confidence: 83%
“…18 Some recent papers report a high success rate with an endoscopic approach for the removal of the migrated band. 28,29 Neto and colleagues 28 reported that endoscopic removal is possible for 85% of patients in the first session with a complication rate of 5.8%. Another study reported that endoscopic removal was attempted in 50 of 63 patients with band erosion, with a 92% success rate and a 10% complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…Without the restriction of the band, most patients regained weight and gastric bypass or biliopancreatic diversion or sleeve gastrectomy was proposed [29][30][31][32]. Some surgeons started to remove the band via laparoscopy and place another band during the same session or several weeks later [33][34][35]. Initially, This was done for intragastric migration of band positioned via the perigastric pathway; pars flaccida positioning was used for the second band.…”
Section: Discussionmentioning
confidence: 99%
“…The band erosion in this study was higher than other studies. 20,24 It was responsible for over one third of complications. …”
Section: Commentsmentioning
confidence: 99%
“…Some studies suggested that it may occur due to overadjustment and chronic pressure on the gastric pouch. 24,27,28 Low experience of surgeon in gastric banding surgeries might be another cause of band erosion. 29 It seems that the shape of the band has significant relation to the rate of erosion.…”
Section: Figurementioning
confidence: 99%